2023
DOI: 10.3390/microorganisms11020274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Long-Term Continuous Cropping of Yongfeng Yam on the Bacterial Community and Function in the Rhizospheric Soil

Abstract: Replant disease caused by continuous cropping commonly occurs in yam with consecutive monoculture. However, little is known about how the continuous cropping of yam affects the rhizospheric soil bacterial community structure. In this study, the effects of continuous cropping on rhizospheric soil characteristics, bacterial diversity, and community structure were investigated in the Yongfeng yam fields under monoculture for 1, 5, 10, 15, and 20 years. Long-term monoculture caused soil acidification and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…This indicated that the changes of soil nutrient content did not affect soil bacterial diversity, but only prompted the growth of some soil bacterial phyla or genera. This is consistent with many previous studies; for example, Yao et al [78] found that the addition of some nutrients increased the richness of soil bacteria in cultivated fields. However, inconsistent with our result, Yao et al [78] also found that the diversity of soil bacteria was suppressed, this may be due to the difference in the experimental geography and wetland ecosystems were a wet ecosystems compared to other ecosystems, and soil nutrient addition would be diluted to a large extent.…”
Section: Differences Of Soil Bacterial Communities In Three Different...supporting
confidence: 93%
See 1 more Smart Citation
“…This indicated that the changes of soil nutrient content did not affect soil bacterial diversity, but only prompted the growth of some soil bacterial phyla or genera. This is consistent with many previous studies; for example, Yao et al [78] found that the addition of some nutrients increased the richness of soil bacteria in cultivated fields. However, inconsistent with our result, Yao et al [78] also found that the diversity of soil bacteria was suppressed, this may be due to the difference in the experimental geography and wetland ecosystems were a wet ecosystems compared to other ecosystems, and soil nutrient addition would be diluted to a large extent.…”
Section: Differences Of Soil Bacterial Communities In Three Different...supporting
confidence: 93%
“…This is consistent with many previous studies; for example, Yao et al [78] found that the addition of some nutrients increased the richness of soil bacteria in cultivated fields. However, inconsistent with our result, Yao et al [78] also found that the diversity of soil bacteria was suppressed, this may be due to the difference in the experimental geography and wetland ecosystems were a wet ecosystems compared to other ecosystems, and soil nutrient addition would be diluted to a large extent. This can explain why these three nature reserves with a higher nutrient content had higher soil bacterial abundance in our study.…”
Section: Differences Of Soil Bacterial Communities In Three Different...supporting
confidence: 93%
“…High-throughput sequencing revealed that bacterial community increased with the increase in continuous cultivation years, consistent with the findings of some studies on other crop species (Zhang et al, 2017;Fei et al, 2021;Jin et al, 2021;Yao et al, 2023). Specifically, the bacterial community composition was dominated by Proteobacteria, Acidobacteria, Actinobacteria, and Gemmatimonadetes at the bacterial phylum level.…”
Section: Soil Microbial Community Changessupporting
confidence: 88%
“…In the farmland ecosystem, long-term continuous cropping of crops would lead to different soil problems-the long-term constant cropping of cotton increases verticillium wilt disease 7 . Longterm monoculture of yam caused soil acidification and increased the potassium and phosphorus concentrations and soil bacterial richness 8 .…”
mentioning
confidence: 99%